Selective Immune Modulating Activities of Viscum album and Its Components; A Possibility of Therapeutics on Skin Rash Induced by EGFR Inhibitors. (September 2022) - Choi, Hye Jin; Park, So-Jung; Choi, You Na; Kim, Soo-Dam; Kwag, Eun-Bin; Song, Si-Yeon; Park, Ji Hye; Kim, Jin Kyu; Seo, Changon; Choi, Jeong June; Yoo, Hwa-Seung
Viscum album var. coloratum (Kom.) Ohwi is a traditional herbal medicine used in East Asia to treat hypertension, skeletal muscle disorders, and cancer. The inhibitory effects of Viscum album (VA) extract on chemokines and its therapeutic potential in erlotinib-induced skin rash were investigated in this study. ELISA was used to measure the levels of chemokines, MCP-1 and RANTES, which are thought to be mediators of erlotinib-induced skin rash in RAW264.7 cells. Western blot analysis was used to look into the activation of signaling pathways like AKT, MAPK, and EGF. In order to investigate the active compounds in VA extract, solvent fractionation and preparative HPLC were performed sequentially. VA extract significantly reduced the production of TNF-α, MCP-1, and RANTES but not IL-1. Furthermore, macrophage transmigration was inhibited without causing cell toxicity. VA extract had no effect on the phosphorylation of EGF receptors stimulated by EGF or suppressed by erlotinib in both A549, a non-small cell lung cancer cells, and Hacat, a human skin keratinocyte. The isolated viscumneoside III and viscumneoside V from VA extract significantly suppressed the expression of MCP-1, according to activity guided fractionation with organic solvent fractionation and preparative HPLC. These findings suggest that VA extract and its active compounds, viscumneoside III and viscumneoside V, regulate MCP-1 production and may have the potential to suppress erlotinib-induced skin toxicity by modulating macrophage activity without neutralizing anti-cancer efficacy.